An approach for description of open educational resources based on semantic technologies - Piedra Pullaguari, N. (2010)
Open Educational Resources are accessed through the web, whose real setting shows an explosion in the use and development of tools and services based on Social Software. However, the growth of this data repository makes it difficult to find information of value, and reduces the possibilities of sharing and exchanging resources. Using semantic technologies to describe educational resources enables any agent (human or software-based) to process and understand its content (applying inference rules on more structured knowledge). Metadata standards can be used to annotate educational resources; they facilitate their interoperability and discovery. In this work, we propose, OER-CC ontology, for the description of Open Educational Resources under Creative Commons Licenses. This approach is based on standard technology and metadata standards. The ontology could be utilized in higher education institutions (and organizations) to facilitate sharing and discovery of their digital content. This electronic document is a live template. The various components of your paper [title, text, heads, etc.] are already defined on the style sheet, as illustrated by the portions given in this document. © 2010 IEEE.